(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2024)
The Islamic financial ecosystems, such as zakat and waqf, have roles in tackling poverty and can be integrated into providing financial protection, such as death benefits to the poor through microtakaful. However, unpredictable payouts and irregular contributions can hinder the implementation of microtakaful, affecting cash flows. This paper employs a system dynamics approach to simulate the cash flows of microtakaful funds, emphasizing the influence of three key factors: the rate of new participants, the mortality rate, and the contribution rate. Note that this approach is chosen for its ability to model complex systems and predict the behavior of microtakaful funds over time. The data collected were from various institutions, including the Life Insurance Association of Malaysia (LIAM), the Central Bank of Malaysia (BNM), and the Department of Statistics Malaysia (DOSM) from 2018 to 2020. The model indicates a minimum contribution rate of RM130 per year, with a 2% mortality rate and 0.8% annual increase in the new participants. The model serves as a foundation for designing a simple and understandable non-profit microtakaful product.